Relative Rates of Gluten Digestion by Nine Commercial Dietary Digestive Supplements - Tanner, Gregory John (Frontiers in Nutrition, 2021)
Endopeptidases containing supplements may digest gluten and reduce the impact on celiac and gluten-sensitive subjects who inadvertently consume gluten. We investigated the relative rate of disappearance of coeliac relevant epitopes, in extracts of nine commercial supplements, using two approved competitive ELISA assays - Ridascreen (detects QQPFP, QQQFP, LQPFP and QLPFP) and Gluten Tec (detects Glia-α20, PFRPQQPYPQ). All epitopes are destroyed by cleavage of P and Q amino-acids. These experiments were designed to measure relative rates of epitope digestion not to mimic in vivo digestion. The supplements were: 1 GluteGuard, 2 GlutenBlock, 3 GliadinX, 4 GlutnGo, 5 GlutenRescue, 6 Eat E-Z Gluten+, 7 Glutenease, 8 Glutezyme, and 9 Gluten Digest. Rates at pH 3.5 and pH 7.0 were measured. The mean initial rate, and half-lives were deduced and extrapolated to rates at the recommended dose of 1 supplement in a fasting stomach volume. At pH 7, supplement 1 was the fastest acting of the supplements, with Ridascreen ELISA, more than twice as fast as the next fastest supplements, 5, 6, 7 and 8. Supplements 2, 3 and 4 showed little activity at pH 7.0. Supplement 1 was also the fastest acting at pH 7 with Gluten-Tec ELISA, more than 3 times the rate for supplements 2 and 3, with supplements 4 to 9 showing minimal activity. At pH 3.5, supplement 1 acted more than five times as fast as the next fastest supplements, 2 and 3, when measured by Ridascreen, but supplements 2 and 3 were over two times faster than supplement 1 when measured by Gluten-Tec. Supplements 4 to 9 demonstrated minimal activity at pH 3.5 with either ELISA. Supplement 1 most rapidly digested the key immuno-reactive gluten epitopes identified by the R5 antibody in the Codex approved competitive Ridascreen ELISA method and associated with the pathology of celiac disease.